THE GLACIOLOGICAL MAPS OF MEIGHEN ISLAND, N.W.T. - Arnold, K. C. (Canadian Journal of Earth Sciences, 1966)
The small ice cap on Meighen Island has been studied since 1959 by scientists working with the Polar Continental Shelf Project, Department of Mines and Technical Surveys, Ottawa. The Surveys and Mapping Branch of the same Department has produced a glaciological map of the ice cap, at the scale of 1:25 000, from special photography taken from a height of 2 280 m in 1960, and a 1:50 000 map of the whole island, showing features of glaciological interest, from standard mapping photography taken from a height of 9 150 m in 1959. The control, photography, and compilation methods used in producing these maps are discussed, and an account is given of the special features shown on them.